Predictors for Intracranial Hemorrhage Following Intravenous Thrombolysis in Posterior Circulation Stroke - Dorňák, Tomáš; Král, Michal; Sedláčková, Zuzana; Šaňák, Daniel; Čecháková, Eva; Divišová, Petra; Zapletalová, Jana; Kaňovský, Petr (Translational stroke research, 2018)
Intravenous thrombolysis (IVT) is a standard treatment for anterior (ACS) and posterior circulation stroke (PCS). However, due to the low occurrence of PCS and of intracranial hemorrhage (ICH) in PCS, the knowledge about ICH predictors following IVT in PCS is sparse. Our aim was to identify predictors for ICH following IVT in PCS. The set consisted of 1281 consecutive ischemic stroke (IS) patients treated with IVT, out of which 158 (103 males; mean age 65.6 ± 12.3 years) had PCS. Collected data include baseline characteristics, common stroke risk factors, pre-medication, stroke severity, admission blood glucose level, blood pressure and treatment with intravenous antihypertensive therapy before and during IVT, occlusion of arteries, recanalization rate, time to treatment, and clinical outcome at day 90. Overall, 11 (7%) patients had ICH. Atrial fibrillation (p = 0.004), neurological deficit at time of treatment in the National Institutes of Health Stroke Scale (p = 0.016), decreased level of consciousness (p = 0.003), occlusion of basilar artery (p = 0.007), occlusion of PCA (p = 0.001), and additional endovascular therapy (p = 0.001) were identified by logistic regression analysis as significant predictors for ICH in PCS. Patients with ischemic lesion in the brainstem, occlusion of vertebral artery, or absence of basilar and posterior cerebral artery occlusion might be considered for treatment with IVT even in borderline cases. Those patients seem to have less frequently favorable outcomes without an increase in ICH rate. Time to IVT in PCS seems not to influence ICH risk or chances for favorable outcomes as significantly as it does in ACS.
Keywords: fibrinolytika; Male; retrospektivní studie; Middle Aged; Intravenous thrombolysis; intravenózní podání; magnetická rezonanční tomografie; Intracranial hemorrhage; Fibrinolytic Agents; magnetická rezonanční angiografie; cévní mozková příhoda; Stroke; Aged; mužské pohlaví; senioři; ischemie mozku; Magnetic Resonance Angiography; Tissue Plasminogen Activator; tkáňový aktivátor plazminogenu; senioři nad 80 let; lidé; ženské pohlaví; Humans; intrakraniální krvácení; Ischemic stroke; Aged, 80 and over; prediktivní hodnota testů; Intracranial Hemorrhages; Retrospective Studies; Magnetic Resonance Imaging; Administration, Intravenous; Female; Posterior circulation; lidé středního věku; Predictive Value of Tests; Brain Ischemia